Pengaruh Workplace Stretching Exercise (WSE) dan Heat Therapy (Hot Pack) terhadap Keluhan Muskuloskletal pada Perawat Tahun 2019 - Eko Syafrianto; Pramana K.H; Zulfa Zulfa (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Musculosceletal disorders are complaints that are often felt by nurses in providing nursing care. One of the most effective ways to overcome this is by providing combination therapy of workplace stretching exercise (WSE) and heat therapy (hot pack). The purpose of this study was to determine the effect of WSE and hot packs on musculosceletal disorders in nurses. This research is a Quasi Experiment Design study with a Two-Group Pre-Post design. The sample in this study were 52 nurses divided into 2 groups using simple random sampling technique. Musculosceletal disorders were measured using nordic body map (NBM). Data analysis used the Wilcoxon statistical and get at a significance level of 95% with test results (p. = 0,000). This shows that there is an influence of WSE and hot pack on musculosceletal disorders in nurses. Nurses are expected to pay more attention to how to work, workload and work facilities properly and do WSE and hot pack regularly.